Intermediate Algebra (12th Edition)

Published by Pearson
ISBN 10: 0321969359
ISBN 13: 978-0-32196-935-4

Chapter 4 - Section 4.3 - Polynomial Functions, Graphs, and Composition - 4.3 Exercises: 23


$f(x)=3x^{3}+x$ and $g(x)=-2x+3$

Work Step by Step

We know that $(f+g)(x)=f(x)+g(x)$. Therefore, we know that the two polynomial functions will have to satisfy the following condition: $f(x)+g(x)=3x^{3}-x+3$ Two such functions that satisfy this condition are: $f(x)=3x^{3}+x$ and $g(x)=-2x+3$ $f(x)+g(x)=(3x^{3}+x)+(-2x+3)=3x^{3}+x-2x+3=3x^{3}-x+3$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.